PENGARUH MEDIA PEMBELAJARAN DIGITAL WORDWALL TERHADAP KEMAMPUAN BERPIKIR SIMBOLIK ANAK USIA 5–6 TAHUN DI TK PERTIWI TONDONGKURA - Nur Afni Adila Sabir; Herman; Fadhilah Afifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of Wordwal digital learning media on the symbolic thinking ability of children aged 5-6 years at TK Pertiwi, Tondongkura Village, Tondong Tallasa Subdistrict, Pangkajene Islands Regency. Symbolic thinking, a core component of early cognitive development, refers to children's ability to recognize and use numerical and alphabetical symbols meaningfully. Preliminary observation indicated that most children in this kindergarten still had difficulty distinguishing number symbols, recognizing letters, and using symbols for counting, and quickly lost interest in monotonous learning methods. A quantitative approach with a quasi-experimental Nonequivalent Control Group Design was employed. Thirty children aged 5-6 years were selected through purposive sampling and divided into an experimental group (n = 15), which received six treatment sessions using the Wordwal Match Up game, and a control group (n = 15), which received conventional activities using blocks and worksheets. Data were collected through observation, tests, and documentation, and analyzed using descriptive statistics and the Wilcoxon Signed Rank Test in SPSS. The experimental group's mean score increased from 13.00 (pre-test) to 20.67 (post-test), with a Wilcoxon test result of Z = -3.457 and Asymp. Sig. (2-tailed) = 0.001 (p < 0.05), while the control group's mean score increased only slightly, from 12.13 to 13.73. These findings indicate that Wordwal-based digital learning media has a significant effect on improving young children's symbolic thinking ability and can be considered an engaging alternative learning tool for early childhood educators